Features and prospects of economic development in India - Hussein Dekan Darwish (Iraqi Journal for Administrative Sciences, 2024)
India is considered one of the main emerging markets in the continent of Asia in the field of activating sustainable economic development processes, adopting economic reform and restructuring policies in the components of the gross domestic product, and contributing to economic openness and interdependence with the rest of the countries of the Asian economic system and the global economic space, as the average annual per capita income reached ( 320 dollars in 1994, which rose to 450 dollars in 2000, with a growth rate of 40, or the economic growth rate of national income during the period - 1994 (1985) reached 3, and the life expectancy rate reached 62 in 1994, and the percentage of educated people (48) The inflation growth rate for the period (1984 - 1994) was (9.7%), and the percentage of workers in the agricultural and industrial sectors was (64-16) respectively in 1990, and the percentage of those enjoying health care and sanitary water was (5550) in 1980 respectively. 1993 Approximately (16) of the population lives in a clean environment, and the child mortality rate is (70) cases for every (1000) births in 1994 and during the period (1995-1989) approximately (63) of children under the age of (5) years suffer from diseases The maternal mortality rate also reached (437) deaths per year. (1000) These numbers and ratios reflect the state of great economic backwardness in India, inefficient economic policies, and the need for an effective and efficient strategy for sustainable economic development.